1993
DOI: 10.1111/j.1365-2265.1993.tb01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for thyroid diseases in an iodine sufficient area with sensitive thyrotrophin assays, and serum thyroid autoantibody and urinary iodide determinations

Abstract: This study provides further information on the prevalence of thyroid dysfunction and autoimmune thyroid diseases in an iodine sufficient area. In addition, it suggests that more than half of the patients with unsuspected hypothyroidism were negative for autoantibodies and that the excessive iodine intake may be involved in causing latent hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
4
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 40 publications
3
62
4
6
Order By: Relevance
“…Seventy percent of the women with hypothyroidism were receiving L-thyroxine. In 1993, Konno et al investigated the prevalence of thyroid dysfunction and its relation to thyroid autoantibodies in apparently healthy people residing in Japan [3]. They reported that the thyroid autoantibodies were positive in 13.8% of females.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy percent of the women with hypothyroidism were receiving L-thyroxine. In 1993, Konno et al investigated the prevalence of thyroid dysfunction and its relation to thyroid autoantibodies in apparently healthy people residing in Japan [3]. They reported that the thyroid autoantibodies were positive in 13.8% of females.…”
Section: Discussionmentioning
confidence: 99%
“…The imprecision deriving from the variability of commercially available assays for TPOAb should also be considered (128). Such limitations must be taken into account when considering the prevalence rate of TPOAb in the general and in the obese population (64,66,129,130,131,132,133,134,135,136,137).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…On the other hand, excessive iodine intake can also lead to thyroid dysfunction. For instance, high iodine intake in China due to the presence of high iodine in drinking water or in Japan due to high seaweed consumption (milligram of iodine intake per day) has been linked with thyroid disorders such as goiter, hypothyroidism, and autoimmune thyroiditis (2)(3)(4)(5)(6). In iodine-deficient areas, increase in iodine intake might precipitate iodine-induced hyperthyroidism (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%